A direct-conversion receiver IC for WCDMA mobile systems. - Reynolds, S.K (IEEE Journal of solid state circuits)
A prototype design of a 2.7-3.3-V 14.5-mA SiGe direct-conversion receiver IC for use in third-generation wide-band code-division multiple-access (3G WCDMA) mobile cellular systems has been completed and measured. The design includes a bypassable low-noise amplifier (LNA), a quadrature downconverter, a local-oscillator frequency divider and quadrature generator, and variable-gain baseband amplifiers integrated on chip. The design achieves a cascaded, LNA-referred noise figure (including an interstage surface acoustic wave filter) of 4.0 dB, an in-band IIP3 of -18.6 dBm, and local-oscillator leakage at the LNA input of -112 dBm. The static sensitivity performance of the receiver IC is characterized using a software baseband processor to compute link bit-error rate.